A multi-agent system embedded to a Product Lifecycle Management to synthesise and reuse industrial knowledge. (15th May 2008) - Gomes, Samuel; Monticolo, Davy; Hilaire, Vincent; Mahdjoub, Morad
This article presents a Knowledge Management experiment carried out in an industrial company. Our research concerns the development of a knowledge engineering module integrated in a Product Lifecycle Management (PLM) system which is based on a multi-domain scheme (project, product, process and use) taking into consideration several viewpoints (structural, functional, dynamic, etc.). This PLM system enables us to capture technical data and information throughout design projects. The development of this PLM system concerns the implementation of knowledge engineering features, using multi-agent technology. This approach allows us to model the collaborative engineering activities and synthesise industrial knowledge during projects (vocabulary, rules, experiences, etc.) using technical information.